Peer Assisted Learning: Dynamics of Anatomic Learning at The Faculty of Medicine Jendral Achmad Yani University - Wendra Wendra (STAI Hubbulwathan Duri, 2021)
Anatomy is a basic science that is important to learn and understand for both clinical students and medical students in general. In addition to studying several biomedical and clinical sciences, a medical faculty student is also required to study and know the anatomical system, where anatomy is one of the mandatory courses that supports science in the health sector, especially to understand the functions in the body. One method that is often used by some universities or colleges when carrying out their anatomy practicum activities is through the Peer Assisted Learning (PAL) method. PAL is a learning method carried out by fellow students and does not involve professional lecturers in the process. This study aims to explore in depth students' perceptions of PAL in the learning process at the Faculty of Medicine, Jendral Achmad Yani University. This study uses an analytical observation method with a descriptive analysis approach, and the results of this study explain that there are various student perceptions regarding the definition and benefits of the PAL method, as well as several factors that influence PAL in the teaching and learning process, including supporting factors such as good communication from students. peer tutors and the material provided by peer tutors is in accordance with the learning objectives. Factors that hinder the PAL implementation process include readiness for implementation, readiness for peer tutors, and readiness for peer tutors. In addition, there are also student perceptions regarding expectations for the implementation of PAL, namely the application of PAL in CSL, the use of technology, and evaluation in its implementation.